التنوين وفاعلية التنكير - حمدان، ابتسام أحمد; زكريا، شحادة (جامعة تشرين, 2016)
يعد هذا البحث استكمالا لكثير من الدراسات التي تناولت التنوين أداة من أدوات تنكير الاسم، إذ بدا اهتمام علماء العربية به واضحا وجليا في مؤلفاتهم وكتبهم، محاولين ضبط أصوله، وتلمس أثره في السياق اللغوي. وقد توقف البحث على أصل التنوين في اللغات السامية عامة، وفي اللغة العربية خاصة، ومن ثم تناول حده اللغوي والاصطلاحي عند النحاة واللغويين والبلاغيين، كما سلط الضوء على أنواعه، واختلاف العلماء حول عددها ودلالة كل نوع منها، مبرزا فاعليته الدلالية في الإشارة إلى تنكير الاسم باعتباره أداة تقابل أداة التعريف (الألف واللام). إضافة إلى إظهار العوائق التي واجهت النحاة كتنوين الأعلام التي هي من المعارف، وصولا إلى التعريف بمواطن حذفه التي حددت من قبل النحاة.
This research is considered a completion to many studies which dealt with nunnation as a tool of namelessness as Arabic scientists were clearly interested in nunnation in their artistic texts and books to control its origins and feel its effect in the lingual context. Research about nunnation origins has stopped in the semetic languages, generally speaking, and in Arabic in particular. After that its linguistic and conventional meaning was known by grammarians, linguals and eloquent people. It also spotlighted all its kinds, the linguists disagreement about its number and indication of each kind of it projecting its significance efficacy in reference to namelessness as a tool that is opposite to the definite article (alef and lam) In addition to show the obstacles that faced grammarians as proper names nunnation which is considered as a part of identifiers to know its omission places which were identified by grammarians.
Keywords: النحو العربي -- اللغة العربية -- السياق اللغوي